A Literature Review to Evaluate the Impact of Machine Learning and Artificial Intelligence for Lung Cancer Patient in COVID-19 Pandemic - Selly Anastassia Amellia Kharis; Arman Haqqi Anna Zili; Fauzan Ihza Fajar; Agustiani Putri; Melisa Arisanty (G-Tech: Jurnal Teknologi Terapan, 2024)
Cancer patients are considered susceptible to COVID-19 associated with the presence of an immunosuppressive state. One type of cancer that causes many deaths is lung cancer. There are many challenges and difficulties, especially in treating lung cancer during the COVID-19 period. As technology develops, experts are trying to use machine learning and artificial intelligence in the treatment and detection of lung cancer. Artificial intelligence and machine learning can be used to predict lung cancer using data from microarrays, pictures, and other sources. Limited data on COVID-19 patients with a relatively small sample, information regarding the implementation of machine learning and artificial intelligence for the treatment of COVID-19 patients with lung cancer is still limited. Therefore, it is necessary to have a literature review to explain the effect of machine learning and artificial intelligence for lung cancer patients during the COVID-19 period from existing studies. The literature review used in this study. Sourced from the search results of journals from various countries related to lung cancer and COVID-19 in Pubmed, Science Direct, and Google Scholar. The results show an important role of machine learning and artificial intelligence for lung cancer patients in COVID-19 pandemic.